Constructive criticism in modern literary studies -: - Hair model - البارز, حازم فاضل محمد (Al-Adab Journal, 2019)
The critical reading in the light of the constructive criticism is listen quietly to the text, including, without changes, to translate this listening later to serious attempts to decode the positive and negative symbols and knowledge of text indications disclosed structures cognitive loaded in it, this brings us to the desire of an independent study in this area which is b (constructive criticism in literary studies HADITHA hair a model), one of the Introduction and pave who was entitled: (Monetary Bannae- definitions entrance), and Study first was entitled: (the concept of constructive criticism in literary studies HADITHA theoretical level), where This section dealt with at the level of endoscopy strategy constructive criticism and objectives of cash, standards and qualifications critic construction and the language of constructive criticism, while the second section was entitled: (function constructive criticism and ways Achtgalh- practical level), where he addressed this topic shifts cash from a knowledge to build and function of constructive criticism and models engage in cash and then we come to the conclusion of the research and a list of sources and references, and a summary in Arabic and English.In light of this thought most of this criticism individual distinctive character, which is based on the criterion of artistic honesty and provisions and to taste the innate sense and net Sliqthm they have taken a measure of all modern literary studies, as well as that constructive criticism is subjective impression through the adoption by the critic on what puts literary impact in himself from the reaction of emotional and psychological neutrality in isolation from many of the rules the literary set, and this cash remains on the different concepts and the multiplicity of Zhoyah, due to the preview and mechanisms functioned, Compass indispensable, and open the road, which is no way to achieve a successful act and sound without it.